The Greek Polis and the invention of democracy : a politico-cultural transformation and its interpretations - Arnason, Johann P.; Raaflaub, Kurt A.; Wagner, Peter, 1956 September 18- (Chicester : Wiley, 2013)
The Greek Polis and the Invention of Democracy presents a series of essays that trace the Greeks' path to democracy and examine the connection between the Greek polis as a citizen state and democracy as well as the interaction between democracy and various forms of cultural expression from a comparative historical perspective and with special attention to the place of Greek democracy in political thought and debates about democracy throughout the centuries. Presents an original combination of a close synchronic and long diachronic examination of the Greek polis.
Solonian Legislation, Political Thinking, and Institutional EvolutionThe "Sophists," especially Protagoras; Democratic "Accounts" and Socratic Self-examination10; Democracy, Philosophy, Eudaimonism; Perfecting Nature, Living with Self-respect: Lysias on the Athenian Past; The Political Eudaimonism of Plato and Aristotle; Conclusion: the Vital Points of Contention; Acknowledgment; 9 Inscriptions and the City in Democratic Athens; Athenian History and Athenian Inscribing to 480 BCE; Athens and Athenian Inscribing from 480 to 403; Athens in the Fourth Century; Abbreviations.
PART III: Changing a Way of Life: Democracy's Impact on Polis Society.
Includes bibliographical references and index.
Print version record.
Keywords: To 1500; Civilization -- Greek influences; Democracy -- Greece -- History -- To 1500.; Arts -- Political aspects -- Greece -- History -- To 1500.; Citizenship -- Greece -- History -- To 1500.; City-states -- Greece -- History -- To 1500.; Civilization -- Greek influences; Democracy -- Greece -- History -- To 1500.; Greece -- Politics and government -- To 146 B.C.; Greece -- Social conditions -- To 146 B.C.; Politics and culture -- Greece -- History -- To 1500.; Social change -- Greece -- History -- To 1500.; Civilization -- Greek influences; Democracy; Politics and government; Greece -- Politics and government -- To 146 B.C.; Greece -- History -- To 146 B.C.; Greece; Electronic books; History